Influence of toxic leadership on turnover intention: The mediating role of psychological wellbeing and employee engagement - Fizza Naeem; Sobia Khurram (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
The purpose of this study is to examine the presence of toxic leadership in banking sector of Pakistan with its influence on various job related outcomes which are psychological wellbeing, employee engagement and turnover intention of employees. Through random sampling technique six conventional private and public banks were selected based on quantitative approach. In total, 393 participants completed a self-completion structured questionnaire based on voluntary participation. Structural Equation Modelling (SEM) technique was employed by using SmartPLS version 3.0. Results supported the presence of toxic leadership in banking sector of Pakistan due to which turnover intention increases. Toxic leaders also seemed to have significant negative influence on psychological wellbeing and employee engagement. Furthermore, the relationship among toxic leadership and employee's turnover intention is partially intervened by psychological wellbeing and employee engagement. Understanding leaders'/supervisors' behavior is essential for banks which assist them in retaining employees by creating an environment that boost their wellbeing and make them engaged in their work. The HR managers should focus on considering employees' feedback regarding their supervisors in the form of survey or one on one interviews which will help in identifying supervisors with toxic traits. This study contributes to the existing literature by studying an understudied emerging concept of toxic leadership and its various consequences in the banking sector of Pakistan. This study is the first to consider toxic leaders as an antecedent of turnover intention in banking sector in Pakistani context.
Keywords: 330; leadership styles; toxic leadership; turnover intention; psychological wellbeing; employee engagement; banks; Pakistan